Good communicators, poor speakers : an exploration of low speech intelligibility and phonological impairment in children and young adults with Down syndrome - Ní Cholmáin, Clothra (Trinity College (Dublin, Ireland). Department of Clinical Speech & Language Studies, 2003)
These studies investigated phonological impairment in 75 children and young adults with Down syndrome (DS) who presented clinically with low speech intelligibility. The first study compared intelligibility levels and phonological development in this group with 75 typically developing children (TD) matched by language age. Comparisons were made between the groups using measures of intelligibility levels, phoneme inventories, percentage of consonants correct and phonological processes. The results indicated that the group with Down syndrome scored significantly lower on all measures of the speech system than the language age-matched typically developing group. The second study explored the phonological systems of 40 participants from the Down syndrome group in greater detail and examined associations between phonological impairment and development in other components of language. This study used rating scales based on constraint rankings from Optimality Theory along with the measures used in the first study to evaluate phonological development and impairment. The British Picture Vocabulary Scale (Dunn, Dunn, Whetton & Pintillie, 1982) was used to establish developmental levels in receptive vocabulary. Subtests from the Test of Auditory Comprehension of Language (Carrow-Woolfolk, 1985) measured receptive morphology and syntax. A speech sample obtained using the Renfrew Action Picture Test (Renfrew, 1989) was used to rate expressive vocabulary, morphology and syntax. Findings indicated significant associations between low speech intelligibility and the phonological system. Associations between phonology and other components of language were also identified.
Keywords: Clinical Speech and Language Studies, Ph.D.; Ph.D. Trinity College Dublin